The future of the WTO after the Nairobi Ministerial Conference - Evita Schmieg; Bettina Rudloff (Stiftung Wissenschaft und Politik (SWP), 2016)
The WTO's 10th ministerial conference took place shortly before Christmas 2015, the first to be held in Africa. Verdicts on its outcomes range from "the death of the Doha Round" to WTO Director-General Roberto Azevêdo's praise for a "historic" package. A more measured assessment reveals a mixed picture. While a number of important decisions were reached in Nairobi, most of the controversial questions were not even on the agenda. And it is less clear than ever where the talks should go from here. A consistent and ongoing shared interest in the global public good of a strong world trade system should persuade the member-states to find constructive new approaches. (SWP Comments)
Keywords: 320